Accelerating studies on the ontogeny and morphological diversity in immature mites - Zhang, Zhi-Qiang (Zootaxa, 2018)
Over 58,000 species of mites have been described (Zhang 2011; Liu et al. 2013). Most species of mites are known only as adults, although immature instars also present a diversity of characters and other information potentially useful for understanding mite taxonomy, phylogeny and biology. A recent overview of juvenile instars of oribatid mites (excluding Astigmata) shows that only about 8% of the known oribatid mites have one or more juvenile instars described (Norton & Ermilov 2014). A survey of papers published during the last three years (2015–2017) in five main acarological journals (Acarina, Acarologia, International Journal of Acarology, Persian Journal of Acarology, Systematic and Applied Acarology) and two other main zoological journals (Zootaxa and ZooKeys) with mite papers showed only 3% to 19% of these with descriptions of immatures, but among the 151 species included in these papers as many as 61% have full data on the ontogeny (Liu & Zhang 2018).